The Influence of Brand Image, Service Quality and Price on Consumer Satisfaction (Study on Consumers of Kopi Kenangan, Tebet) - Natalia Rosauli Basa Simanjuntak; Djumarno Djumarno (International Journal of Social Service and Research (IJSSR), 2023)
This research was conducted to determine the effect of brand image, service quality and price on customer satisfaction and its effect on customer loyalty. The object of this research is Kopi Kenangan, Tebet. This research was conducted on 150 respondents using a quantitative descriptive method. Therefore, the data analysis used is statistical analysis in the form of Smart PLS. The results of this study indicate that the brand image variable has a positive and insignificant effect on customer satisfaction, service quality has a negative and insignificant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction, brand image has a positive and insignificant effect on customer loyalty, quality service has a negative and insignificant effect on customer loyalty, price has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, brand image through customer satisfaction has a positive and significant effect not significant effect on customer loyalty, service quality through customer satisfaction negative and insignificant effect on consumer loyalty, price through customer satisfaction has a positive and significant effect on customer loyalty.